Adaptation Strategies to Climate Change in the Gum Arabic Belt of North Kordofan, Sudan - Khalifa, Awad Elkarim S.O.; Sanjak, Elamin; Ibrahim, Abdelateif H.; Mirghani, Omima A.; A. A, Asmamaw (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Climate change will, in many parts of the world, adversely affect socio-economic sectors, whichinclude water resources, agriculture, forestry, fisheries and human settlements, ecological systemsand human health, developing countries are the most vulnerable. During the last three decades,North Kordofan has experienced catastrophic and frequent droughts with far-reachingconsequences on agricultural and pastoral systems, regional economy, traditional family livelihoodand environment the climate change studies in Sudan are not well – known to a lot of people. Themain objective of this paper was to investigate the climate change adaptation strategies adopted bylocal communities in the gum Arabic belt of North Kordofan State (Bara Locality). It tried toexamine the impact of the climate change on agricultural production and securing food supply.The primary data was collected through face-to-face interview with local people, group discussionwith key informants, and personal observations. A number of 140 respondents were selectedamong 697 household from six villages in Bara Locality using multiple stage random sampling.The data were analyzed using descriptive statistics, t-test and logistic regression. The main findingsof the study showed that the adaptation strategies for improving crop production were, usingimproved seeds (43.6%), crop rotation (42.1%), fallow period (81.4%) and early planting (1.4%).The adaptation strategies for food security and poverty reduction were, reducing meals (15%),using alternative food (95%), plantation of Hyphenetheibica (11.4%) and fisheries (40%). Theadaptation strategies for livestock production and rangeland management were, using alternativefeed (94.3%), fences (35%), changing animal type (26.4%) and grass seed broadcasting to enrichthe range (39.3%). The adaptation strategies for forestry and natural resource conservation were,expansion of A. senegal plantations (42.9%), establishment of gum Arabic production associations(18.6%), shelterbelts (40%), energy alternatives (40.7%), change of traditional houses (74.3%) andadoption of communal forests (10%). The results from logistic regression model revealed thathousehold socio-economic factors were the main determining factors that influencing farmer’choice and adaptation strategies. The main conclusion drawn from this study is, climate change isrecognized as a real challenge for the sustainable livelihood of local communities in the study area, and the adaptation strategies taken by the local inhabitants are not enough to face such change.This necessitates the intervention of the different governmental institutions to enhance the locallydriven adaptation options by local communities enforce a newline.